Marginalized Margins. - Mothersill, M. Gillian (International Journal of the Book)
Have margins become ‘marginalized’, or are they simply taking different forms in the e-book or online book? This paper investigates the design and economic history of the margin in book layout and typography. The paper presents reasons for the declining use of the margin in current book layouts, and explores issues that result when white space is reduced. New forms of margins, in online books and e-books are evaluated, with emphasis on readability, user-friendliness and economic considerations.